Analisis Perbandingan Tingkat Kesehatan Bank Syariah Devisa dan Non Devisa Dengan Menggunakan Metode Camel : Studi Kasus PT Bank Syariah Mega Indonesia dan PT Bank Rakyat Indonesia Syariah Tahun 2009-2010 - Mutia Ramadhani; Isfandayani . (MASLAHAH (Jurnal Hukum Islam dan Perbankan Syariah), 2014)
The purpose of this study was to determine the health of banks using the CAMEL and compare the results between Islamic banks and non-foreign exchange. The benefits of this research are expected to be material contribute ideas about the role and functions of financial management, especially in one of the functions that determine the health of banks. The method used is qualitative naturalistic method with secondary data sources (secondary data) are available on the Bank's internet service Indonesia.CAMEL is the rating that is based on five factors: Capital, Assets, Management, Earnings, and Liquidity. But in this research method used is due to limited scope CAMEL researchers, management aspects are considered 100% in the assessment. The conclusion from this study showed that foreign Islamic banks that have greater access to running services relating to transactions in foreign currencies, which are represented by PT. Bank Syariah Mega Indonesia in 2009 in a healthy position, as well as in 2010. Based on the calculation of capital ratios for two years, namely 2009 and 2010 PT. BSMI obtain CAR, BDR, KAP, ROA, ROA, CR, and LDR at position 100% healthy.